Democracy in divided societies : electoral engineering for conflict management - Reilly, Ben (Theories of institutional design., 2001)
Reilly analyses the design of electoral systems for divided societies, examining various divided societies which utilise 'vote-pooling' systems - including Sri Lanka, Northern Ireland and Fiji. Political institutions which encourage broad-based, aggregative political parties can, under certain conditions, encourage moderate, accommodatory political competition - influencing the trajectory of democratization in transitional states.